2022
DOI: 10.1126/sciadv.abn0832
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ciliogenesis-associated CPLANE complex

Abstract: Dysfunctional cilia cause pleiotropic human diseases termed ciliopathies. These hereditary maladies are often caused by defects in cilia assembly, a complex event that is regulated by the ciliogenesis and planar polarity effector (CPLANE) proteins Wdpcp, Inturned, and Fuzzy. CPLANE proteins are essential for building the cilium and are mutated in multiple ciliopathies, yet their structure and molecular functions remain elusive. Here, we show that mammalian CPLANE proteins comprise a bona fide complex and repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 86 publications
(132 reference statements)
1
23
0
Order By: Relevance
“…A recent study carried out on mice and human cell lines has revealed that the complex adopts a crescent-like architecture, such that Wdpcp and Rsg1 are located at the ends of the crescent and bind to the central Intu-Fuz heterodimer on opposite sides. This creates a linear-type subunit interaction scheme that can be represented as Wdpcp-Intu-Fuz-Rsg1 [ 28 ].…”
Section: Cplane Complex Structurementioning
confidence: 99%
See 4 more Smart Citations
“…A recent study carried out on mice and human cell lines has revealed that the complex adopts a crescent-like architecture, such that Wdpcp and Rsg1 are located at the ends of the crescent and bind to the central Intu-Fuz heterodimer on opposite sides. This creates a linear-type subunit interaction scheme that can be represented as Wdpcp-Intu-Fuz-Rsg1 [ 28 ].…”
Section: Cplane Complex Structurementioning
confidence: 99%
“…Regarding the structure of the different proteins that conform the complex, Wdpcp (85.084 kDa) folds into a seven-bladed β-propeller belonging to the WD40 family, followed by an array of α helices [ 28 ]. Both Intu and Fuz have three longin-like domains (LD).…”
Section: Cplane Complex Structurementioning
confidence: 99%
See 3 more Smart Citations